2019
DOI: 10.1101/757427
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Control of clathrin-mediated endocytosis by NIMA family kinases

Abstract: Endocytosis, the process by which cells internalize plasma membrane and associated cargo, is regulated extensively by posttranslational modifications. Previous studies suggested the potential involvement of scores of protein kinases in endocytic control, of which only a few have been validated within their native context. Here we show that the conserved NIMA-related kinases NEKL-2/NEK8/9 and NEKL-3/NEK6/7 (the NEKLs) control clathrin-mediated endocytosis in C. elegans. Loss of NEKLs leads to clathrin mislocali… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 138 publications
0
7
0
Order By: Relevance
“…The unstructured interdomain linkers of FCHO1, FCHO2, and SH3-containing GRB2-like protein 3-interacting protein 1 (sgip1) have been proposed to interact with AP2 ( 11 , 16 , 26 , 42 ). Biolayer interferometry (BLI) under near-physiological conditions, where AP2 core is known to be in its closed cytosolic conformation ( 14 ), showed that the K D values for the direct interactions between AP2core and FCHO2 linker and between AP2core and FCHO1 linker were ~10 μM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…The unstructured interdomain linkers of FCHO1, FCHO2, and SH3-containing GRB2-like protein 3-interacting protein 1 (sgip1) have been proposed to interact with AP2 ( 11 , 16 , 26 , 42 ). Biolayer interferometry (BLI) under near-physiological conditions, where AP2 core is known to be in its closed cytosolic conformation ( 14 ), showed that the K D values for the direct interactions between AP2core and FCHO2 linker and between AP2core and FCHO1 linker were ~10 μM (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Our lack of understanding of the adaptation of endocytosis under stress conditions goes hand in hand with our limited knowledge about endocytic regulation in other physiological conditions. Even though numerous kinase pathways have been implicated in the regulation of endocytosis [27,117] including some recent additions like the NIMA family kinases in C. elegans [118], how different signal transduction cascades modulate specific endocytic factors and cargo sorting in most cases has remained enigmatic. In addition to phosphorylation, ubiquitination events play a critical role in regulating the uptake of specific cargo proteins.…”
Section: Discussionmentioning
confidence: 99%
“…C . elegans NEKL-2 and NEKL-3 control clathrin-mediated endocytosis and trafficking in non-ciliated cells [ 69 71 ]. NEKL-4 localizes to the periciliary membrane compartment, an active site of endocytosis, a process necessary for regulating ciliary membrane volume, ciliary protein levels, and IFT [ 72 ].…”
Section: Discussionmentioning
confidence: 99%